2016
DOI: 10.1080/10826084.2016.1212890
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Mind in Substance Users: A Systematic Minireview

Abstract: Despite the lack of studies and the methodological limitations of the existing ones Theory of Mind seems to play a role in drug use conditions, which requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
1
18
1
Order By: Relevance
“…In this regard, we suggest caution when comparing our results with those of other studies, including study results from highly educated samples. Sixth, we found lower MMSE and IQ scores in comparison to those values reported for the participants from European and North American studies (Sanvicente-Vieira et al, 2017). It is important to recognize that there were no group-wide differences regarding general intelligence in our study.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…In this regard, we suggest caution when comparing our results with those of other studies, including study results from highly educated samples. Sixth, we found lower MMSE and IQ scores in comparison to those values reported for the participants from European and North American studies (Sanvicente-Vieira et al, 2017). It is important to recognize that there were no group-wide differences regarding general intelligence in our study.…”
Section: Discussioncontrasting
confidence: 58%
“…Emotion recognition is one of the core components of ToM (Ahmed & Stephen Miller, 2010;McDonald et al, 2013), and this function has been shown to be impaired in substance use disorders (Kornreich et al, 2003;McDonald et al, 2013;Sanvicente-Vieira et al, 2017), leading some authors to suggest that sociocognitive impairments may underlie the social dysfunctions found in individuals with substance use disorders (Homer et al, 2008;Volkow et al, 2011a). Consistent with this hypothesis, sociocognitive performance has been suggested to be a predictor of clinical outcomes (e.g., dependence severity, number of hospitalizations), and it has been proposed that there is an association between social cognition and addiction (Fernández-Serrano et al, 2010;McDonald et al, 2013;Sanvicente-Vieira et al, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical studies have demonstrated a relationship between deficits in ToM and deficits in EF. An association between ToM and EF has been shown in autism disorders (Baron-Cohen, 1995;Fisher & Happé, 2005), maternal mental illness (Rigby, Conroy, Miele-Norton, Pawlby, & Happé, 2016) and in SUD populations (Sanvicente-Vieira, Romani-Sponchiado, Kluwe-Schiavon, Brietzke, Araujo et al, 2017;Verdejo-Garcıa, López-Torrecillas, de Arcos, & Pérez-Garcıa, 2005). Although there are few studies that have explored the explicit relationship between RF and EF, several studies make implicit inferences of possible associations, which lead us to suggest a relationship between the capacities.…”
Section: Introductionmentioning
confidence: 99%
“…2,4,10 Additionally, the negative cognitive effects of ATS have been the subject of recent studies. 12 Worse still is the fact that ATS consumers are usually polydrug users, 11 thus increasing their health risks, such as sexual risk behaviors, which might lead to unfavorable outcomes. 13 In addition, previous studies have shown that socioeconomic and demographic characteristics can also have an impact on ATS consumption, acting either as protective factors against or risk factors for drug use and the development of addiction.…”
Section: Introductionmentioning
confidence: 99%